MEMBANGUN PERILAKU EKOLOGIS DI KALANGAN SISWA SMA TARSISIUS JAKARTA - Tumanggor, Raja Oloan (Jurnal Serina Abdimas, 2023)
The environmental conditions in Jakarta are in an alarming situation. When the rainy season arrives, it's no longer unusual for the city of Jakarta to experience flooding, forcing residents who are affected by the floods to leave their homes to save themselves. Floods occur due to increased water discharge in the city of Jakarta, but do not immediately seep into the earth because they are hampered by garbage. A lot of garbage piled up in Jakarta is caused by the behavior of its residents who are not disciplined in disposing of garbage. They do not have ecological behavior or behavior to keep the environment clean and maintain the beauty of the surrounding environment. One group of Jakarta residents who need to have ecological behavior is teenagers who are still in senior high school (SMA). This psychoeducation which was attended by 20 teenagers who attended Tarsisius Jakarta High School explained what efforts could be made to grow and build ecological behavior for teenagers. The purpose of this psychoeducation is to encourage and motivate students to continue to behave ecologically in everyday life in the form of simple behavior through energy saving, transportation, disposing of waste, recycling, consumerism and conservation behavior. Kondisi lingkungan di Jakarta berada pada situasi yang memprihatinkan. Bila musim hujan tiba, maka bukan hal aneh lagi bila kota Jakarta mengalami banjir yang membuat warga yang kena banjir harus meninggalkan rumahnya untuk menyelamatkan diri. Banjir terjadi karena debit air yang meningkat di kota Jakarta, namun tidak segera meresap ke bumi karena dihambat oleh sampah. Banyak sampah bertumpuk di Jakarta disebabkan oleh perilaku warganya yang tidak disiplin dalam membuang sampah. Mereka tidak memiliki perilaku ekologis atau perilaku untuk menjaga kebersihan lingkungan serta memelihara keasrian lingkungan sekitarnya. Salah satu kelompok warga Jakarta yang perlu memiliki perilaku ekologis adalah para remaja yang masih duduk di sekolah menengah atas (SMA). Psikoedukasi yang diikuti oleh 20 orang remaja yang duduk di SMA Tarsisius Jakarta ini menjelaskan upaya apa yang bisa dilakukan untuk menumbuhkan dan membangun perilaku ekologis bagi para remaja. Tujuan psikoedukasi ini adalah mendorong dan memotivasi para siswa untuk tetap berperilaku ekologis dalam hidup sehari-hari dalam bentuk perilaku yang sederhana melalui hemat energi, transportasi, membuang limbah, daur ulang, konsumerisme dan perilaku konservasi.